Optimization of scintillator–reflector optical interfaces for the LUT Davis model. Issue 9 (3rd August 2021) - Trigila, Carlotta; Roncali, Emilie
Abstract: Purpose: Designing and optimizing scintillator‐based gamma detector using Monte Carlo simulation is of great importance in nuclear medicine and high energy physics. In scintillation detectors, understanding the light transport in the scintillator and the light collection by the photodetector plays a crucial role in achieving high performance. Thus, accurately modeling them is critical. Methods: In previous works, we developed a model to compute crystal reflectance from the crystal 3D surface measurement and store it in look‐up tables to be used in the Monte Carlo simulation software GATE. The relative light output comparison showed excellent agreement between simulations and experiments for both polished and rough surfaces in several configurations, that is, without and with reflector. However, when comparing them at the irradiation depth closest to the photodetector face, rough crystals with a reflector overestimated the predicted light output. Investigating the cause of this overestimation, we optimized the LUT algorithm to improve the reflectance computation accuracy, especially for rough surfaces. However, optical Monte Carlo simulations carried out with these newly generated LUTs still overestimate the light output. Based on previous observations, one probable cause is the erroneous assumption of perfect couplings between the reflector and crystal and between the crystal and photodetector, which likely results in an important overestimation of the light output compared to experimental values. In practice, several factors could degrade it. Here, we investigated possible suboptimal optical experimental configurations that could lead to a degraded light collection when using Teflon or ESR reflectors coupled to the crystal with air or grease. We generated look‐up tables with a mixture of air and grease and showed the effect of three possible sources of light loss: the presence of a small gap between the crystal and the reflector edges close to the photodetector face, the infiltration of grease in the crystal–reflector coupling, and the presence of inhomogeneities in the photodetector–crystal interface. Results: The strongest effect is linked to the presence of a small gap of grease between the edges of the reflector material and the crystal (light loss of 10%–12% for 0.2 mm gap). The optical grease infiltrating the crystal–reflector air coupling decreases the light output, depending on the infiltration's extent and the amount of grease infiltrated. Five percent of air in the crystal–photodetector coupling can cause a light output decrease of 2% to 4%. The individual and combined effect of these advanced models can explain the discrepancy of the relative light output obtained with ESR in simulations and experiments. With Teflon, the study indicates that the light output loss strongly depends on the reflectance deterioration caused by grease absorption. Conclusions: Our results indicate that when studying scintillation detector performance with different finishes, performing simulations in ideal coupling conditions can lead to light output overestimation. To perform an accurate light output comparison and ultimately have a reliable detector performance estimation, all potential sources of practical limitations must be carefully considered. To broadly enable high‐fidelity modeling, we developed an interface for users to compute their own LUTs, using their surface, scintillator, and reflector characteristics.